Solution and Gas‐Phase Acidities of all‐trans (all‐E) Retinoic Acid: An Experimental and Computational Study. Issue 31 (17th June 2015) - Abboud, José‐Luis M.; Koppel, Ilmar A.; Uggerud, Einar; Leito, Ivo; Koppel, Ivar; Sekiguchi, Osamu; Kaupmees, Karl; Saame, Jaan; Kütt, Karl; Mishima, Masaaki
Abstract Retinoic acid is of fundamental biological importance. Its acidity was determined in the gas phase and in acetonitrile solution by means of mass spectrometry and UV/Vis spectrophotometry, respectively. The intrinsic acidity is slightly higher than that of benzoic acid. In solution, the situation is opposite. The experimental systems were described theoretically applying quantum chemical methods (wave function theory and density functional theory). This allowed the determination of the molecular structure of the acid and its conjugate base, both in vacuo and in solution, and for computational estimates of its acidity in both phases.